Macrophage Cx43 Is Necessary for Fibroblast Cytosolic Calcium and Lung Fibrosis After Injury - Bhattacharyya, Aritra; Torre, Paola; Yadav, Preeti; Boostanpour, Kaveh; Chen, Tian Y.; Tsukui, Tatsuya; Sheppard, Dean; Muramatsu, Rieko; Seed, Robert I.; Nishimura, Stephen L.; Jung, James B.; Tang, Xin-Zi; et al. (Frontiers in Immunology, 2022)
Macrophages are paracrine signalers that regulate tissular responses to injury through interactions with parenchymal cells. Connexin hemichannels have recently been shown to mediate efflux of ATP by macrophages, with resulting cytosolic calcium responses in adjacent cells. Here we report that lung macrophages with deletion of connexin 43 (Mac-Cx43-KO) had decreased ATP efflux into the extracellular space and induced a decreased cytosolic calcium response in co-cultured fibroblasts compared to WT macrophages. Furthermore, Mac-Cx43-KO mice had decreased lung fibrosis after bleomycin-induced injury. Interrogating single cell data for human and mouse, we found that P2rx4 was the most highly expressed ATP receptor and calcium channel in lung fibroblasts and that its expression was increased in the setting of fibrosis. Fibroblast-specific deletion of P2rx4 in mice decreased lung fibrosis and collagen expression in lung fibroblasts in the bleomycin model. Taken together, these studies reveal a Cx43-dependent profibrotic effect of lung macrophages and support development of fibroblast P2rx4 as a therapeutic target for lung fibrosis.